2011
DOI: 10.1111/j.1751-7915.2011.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient aerobic succinate production from glucose in minimal medium with Corynebacterium glutamicum

Abstract: SummaryCorynebacterium glutamicum, an established industrial amino acid producer, has been genetically modified for efficient succinate production from the renewable carbon source glucose under fully aerobic conditions in minimal medium. The initial deletion of the succinate dehydrogenase genes (sdhCAB) led to an accumulation of 4.7 g l−1 (40 mM) succinate as well as high amounts of acetate (125 mM) as by‐product. By deleting genes for all known acetate‐producing pathways (pta‐ackA, pqo and cat) acetate produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 55 publications
4
89
1
3
Order By: Relevance
“…The resulting DNA fragments served as the template for an overlap extension PCR with oligonucleotides ⌬ldhA1-for and ⌬ldhA4-rev, forming a PCR product of about 1 kb which was digested with the restriction enzymes HindIII and EcoRI and cloned into pK19mobsacB cut with the same enzymes. The construction of the plasmids for the in-frame deletions of pta-ack (⌬pta-ack) and pqo (⌬pqo) was described previously (32). Plasmid pK19mobsacB-⌬cat was kindly provided by V. F. Wendisch (University of Bielefeld).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting DNA fragments served as the template for an overlap extension PCR with oligonucleotides ⌬ldhA1-for and ⌬ldhA4-rev, forming a PCR product of about 1 kb which was digested with the restriction enzymes HindIII and EcoRI and cloned into pK19mobsacB cut with the same enzymes. The construction of the plasmids for the in-frame deletions of pta-ack (⌬pta-ack) and pqo (⌬pqo) was described previously (32). Plasmid pK19mobsacB-⌬cat was kindly provided by V. F. Wendisch (University of Bielefeld).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR product (1 kb) was digested with NdeI and NheI and cloned into pAN6 cut with the same enzymes. Plasmid pAN6-pyc P458S was described elsewhere (32). The construction of plasmid pEKEx2-fdh was performed by amplifying the fdh gene from plasmid pBBR1MCS2-fdh using the oligonucleotide pair fdhPstI-RBS-for and fdh-BamHI-rev.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent metabolic engineering studies have shown that C. glutamicum is also capable of producing a variety of other commercially interesting compounds, e.g., other L-amino acids (4), D-amino acids (5), organic acids such as succinate (6)(7)(8)(9), diamines such as cadaverine (10,11) or putrescine (12), biofuels such as ethanol or isobutanol (13)(14)(15), and proteins (16)(17)(18).…”
mentioning
confidence: 99%
“…18) It has been reported that succinic acid production has been achieved using recombinant microorganisms, such as Escherichia coli [19][20][21][22][23][24][25][26] and Corynebacterium glutamicum. [27][28][29] Moreover, natural succinic acid-producing microorganisms have been isolated, including Actinobacillus succinogenes 30) and Mannheimia succiniciproducens.…”
mentioning
confidence: 99%